Clinical outcomes of patient navigation performed by nurses in the oncology setting: an integrative review - Rodrigo Lima Rodrigues; Franciane Schneider; Luciana Puchalski Kalinke; Silvana Silveira Kempfer; Vânia Marli Schubert Backes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to evidence the clinical outcomes of navigation performed by nurses in cancer patients. Methods: this is an integrative literature review with collection in MEDLINE via PUBMED, LILACS, Web of Science, Scopus, and CINAHL databases. The final sample consisted of seven studies. The data were analyzed and presented descriptively. Data related to clinical outcomes were compiled and described in full. The Agency for Healthcare Research and Quality categorization was used to assess the level of evidence. Results: the clinical outcomes demonstrated were decreased distress, anxiety and depression, improved control and management of symptoms, improved physical conditioning, improved quality and continuity of care, improved quality of life, reduced time to start treatment. Final considerations: there is research that shows better clinical outcomes in cancer patients through navigation by nurses across the continuum of health care.